An approach towards an improvement of genetic structure of a wisent (Bison bonasus) population in the Carpathians (European Bison Conservation Newsletter, 2021)
An important aspect in maintaining small, closed populations, is conservation of their genetic variability. The wisent (European bison) belongs to species with extremely narrw gene pool, since it present world population originates from only 12 founders. About 40% of wisent population maintained in captivity, is included into a breeding program depending on an exchange of individuals based upon pedigree analyses. The genetic structure of free ranging populations though, can be assessed only with molecular markers. Therefore the genetic enrichment of free ranging wisent populations is performed through an import of animals, mostly from captivity. An interesting example of such population, where the program for an improvement of genetic pool is carried out, are wisent herds at Bieszczady Mountains (south-east of Polish Carpathians), created in 60s and 80s, with animals originating from Polish breeding centers. The evaluation of the genetic structure of their initial groups revealed the lack or very low participation of several founders of the contemporary species. In order to improve the gene pool, between 2000–2014, over 30 individuals with known pedigree, were brought there from foreign breeding centers. On the basis of pedigree analysis, assessed was a potential change in genetic structure of this population, resulting from those introductions. The true effect though, will depend on the reproductive success achieved by introduced individuals.
Keywords: Genetic variability; management; Carpathians